Atomistic insights into the mechanical anisotropy and fragility of monolayer fullerene networks using quantum mechanical calculations and machine-learning molecular dynamics simulations. (January 2023) - Ying, Penghua; Dong, Haikuan; Liang, Ting; Fan, Zheyong; Zhong, Zheng; Zhang, Jin
Abstract: In this work, we comprehensively study the mechanical properties of the newly synthesized monolayer quasi-hexagonal-phase fullerene (qHPF) membrane [Hou et al., 2022] under uniaxial tension by using quantum mechanical density-functional-theory (DFT) calculations and molecular dynamics (MD) simulations with a machine-learned neuroevolution potential (NEP). The elastic properties and fracture behaviors of monolayer qHPF are found to be strongly anisotropic due to the different properties between the inter-fullerene C–C single bonds and [2 + 2] cycloaddition bonds. Moreover, the tensile strength and fracture strain of monolayer qHPF are much smaller than those of any other existing two-dimensional (2D) carbon crystals. The very small tensile strength or fracture strain is ascribed to the inhomogeneous deformation of the stretched monolayer qHPF, which originates from the stiffness difference between the soft inter-fullerene bonds and the rigid intra-fullerene bonds. Compared with DFT calculations at the ground state, the NEP-based extensive MD simulations predict a much smaller tensile strength and fracture strain for monolayer qHPF due to their consideration of the effects of temperature and membrane size. Our work not only reveals the underlying mechanism of the fracture behaviors of monolayer fullerene networks from an atomistic perspective, but also shows the effectiveness and accuracy of the NEP approach in determining the mechanical properties of 2D materials in the realistic situations.